Robustness analysis of model parameters for sediment transport equation development - Nadiatul Adilah, Ahmad Abdul Ghani; Duratul Ain, Tholibon; Junaidah, Ariffin (Akademi Sains Malaysia, 2019)
Robustness analysis of model parameters for sediment transport equation development is carried out using 256 hydraulics and sediment data from twelve Malaysian rivers. The model parameters used in the analyses include parameters in equations by Ackers-White, Brownlie, EngelundHansen, Graf, Molinas-Wu, Karim-Kennedy, Yang, Ariffin and Sinnakaudan. Seven parameters in five parameter classes were initially tested. Robustness of the model parameters was measured on the statistical relations through Evolutionary Polynomial Regression (EPR) technique and further examined using the discrepancy ratio of the predicted versus the measured values. Results from analyses suggest